2022
DOI: 10.3390/phycology2010005
|View full text |Cite
|
Sign up to set email alerts
|

Production of Scenedesmus almeriensis Using Pilot-Scale Raceway Reactors Located inside a Greenhouse

Abstract: The microalga S. almeriensis was produced in spring and summer using 80 m2 raceway reactors located inside a greenhouse in Almería, Spain. This microalga was selected because it is a fast-growing and robust strain with potential applications in the production of functional foods and feeds or as a high-value agricultural biostimulant. Overall, the biomass productivity obtained in summer was 24.9 ± 0.9 g·m−2·day−1. This value was higher than that obtained in spring, with an average value of 21.4 ± 1.3 g·m−2·day−… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…The productivity was significantly affected by the environmental conditions and varied depending on the mean irradiance and temperature of the culture. Results were comparable to those reported by Morillas-España et al, who obtained biomass productivity values of 24 g•m -2 •day -1 day when producing the microalga S. almeriensis in raceway reactors of the same volume 21 . Another study reported that Eustance et alt.…”
Section: Effect Of Environmental Conditions On the Biomass Productivitysupporting
confidence: 90%
“…The productivity was significantly affected by the environmental conditions and varied depending on the mean irradiance and temperature of the culture. Results were comparable to those reported by Morillas-España et al, who obtained biomass productivity values of 24 g•m -2 •day -1 day when producing the microalga S. almeriensis in raceway reactors of the same volume 21 . Another study reported that Eustance et alt.…”
Section: Effect Of Environmental Conditions On the Biomass Productivitysupporting
confidence: 90%
“…It is important to stress that assessment of the effect of environmental conditions on macromolecular composition is better understood in outdoor cultures. Morillas-España et al [ 99 ] have shown that the macromolecular composition of Scenedesmus almeriensis cultivated in outdoors raceways under spring and summer using commercial fertilizers as a source of nutrients, showed no major differences with an average protein, lipid, ash, and carbohydrate content of 37.9, 4.6, 10.8, and 46.7%, respectively.…”
Section: Production Of Microalgae Biomass Enriched In Carbohydratesmentioning
confidence: 99%
“…The production of microalgae has tripled in the last 5 years [13]. The interest in world production is due to some characteristics such as high photosynthetic efficiency, fast growth rate, resistance to various contaminants, and the capacity to grow on non-arable lands and be cultured using different growth conditions (autotrophic, heterotrophic, and mixotrophic growth modes) [14,15]. Specifically, previous studies have shown that mixotrophic conditions using different organic carbon substrates improve enzyme production and the T. obliquus biomass yields [16,17].…”
Section: Introductionmentioning
confidence: 99%